Cellulose - Medical, Pharmaceutical and Electronic Applications - Theo van de Ven; Louis Godbout (IntechOpen, 2013)
This book on cellulose, the second in a series of three, deals with the many applications of cellulose, both established ones and those that are emerging. It shows the richness in the way cellulose can be modified to serve a large variety of functions, varying from medical, pharmaceutical and bioelectronics applications. We hope that with these examples the imagination of the reader is stimulated and may him- or herself attempt to find new, fascinating applications of cellulose.
English
Keywords: Physical Sciences; Engineering and Technology; Chemistry; Bioorganic Chemistry; Organic Chemistry